Konvertera Pixlar till Linjer - Samaha, Erik; Cheng, Min (My University, 2017)
This thesis was performed at Chalmers University of Technology, with the background of developing a robot that, based on an image, can draw a portrait of an individual or a group of people. Raspberry Pi is used as a platform for hardware and software which is developed with the programming language Python. The most essential problem has been to convert the original image into a format that deletes backgrounds, colors and shades, and highlights contours. The idea behind this thesis was developed by Sakib Sistek from Chalmers University of Technology. Within this project, a system has been developed able to photograph a face and after image processing draw a sketch of the face with a robot arm. In the final system, OpenCV library was used to convert an image from pixels to lines. The choice of OpenCv is based on an analysis of existing open source programs for image processing. The operating system installed on the Raspberry Pi is based on Linux. The robot arm has managed to draw out the linearized images loaded to it. The sketches drawn by the system became adequately clear enough to identify the person photographed using the Pi-camera connected to the system. Within the project, the Windows 10 IoT Core operating system has been tested, but it did not wort for the purpose of this project. The robot arm used during the project is a pre-ordered kit with its own software. All software used during the work is open source.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science